The Implementation of Islamic Education in Muslim Minority Area - Ike Apriliani; Trivena Justitia (Nazhruna: Jurnal Pendidikan Islam, 2021)
Mainstream educational research in Indonesia is still focused on several fields and assumes a Muslim majority scale. However, there is a reality that on a Muslim minority scale it doesn’t rule out the existence of an Islamic educational institution, which runs side by side with adherents of other religions, can not be ruled out. This essay uses qualitative research with a variety of case studies. The data collection technique was undertaken by interview, observation, and documentation. The subjects in this study were the head of the foundation, the director, the secretary, the education bureau, and several teachers at the La-Royba Bali Bina Insani Islamic Boarding School. In this study, it was found that management education in Islamic boarding schools has always been the main concern. The Islamic religious education curriculum developed at the school, located in a Muslim minority area, consistently pays attention to the demands and conditions of the communal environment. Further, the curriculum also attends to the needs of the students in facing the future, both on a local and global scale.